EFFECT OF MORPHOLOGY ON ELECTRONIC PROPERTIES OF THE <111> -ORIENTED GaAs, GaP, GaSb, InAs, InP AND InSb NANOWIRES - D. A. Yatsyna; D. B. Migas; Y. S. Arsitov; A. B. Filonov; B. S. Kolosnitsyn (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of calculations by means of the first principles methods of the -oriented GaP, GaAs, GaSb, InP, InAs, and InSb nanowires with zince-blende structure show that the morphology of nanowires affects their electronic properties. It has been established that for nanowires with {011} facets the formation of small-sized {112} edges between adjacent {011} facets results in a stable structure and removes the surface states in the band-gap area without the hydrogen passivation.